IS A PARADIGM SHIFT IN MAINSTREAM ECONOMICS NEEDED IN THE LIGHT OF DEVELOPMENTS IN ARTIFICIAL INTELLIGENCE ? - Noga, Marian; Noga, Beniamin (Torun International Studies, 2024)
Economic researchers have been discussing a paradigm shift in mainstream economics for many years, as economics as a science has ceased to formulate accurate predictive conclusions. Representatives of unorthodox streams of economics, such as institutional economics, behavioural economics or the emerging neuroeconomics, state that the classical paradigm of mainstream economics should be eliminated from research and a new paradigm of economics should be introduced into economic science. Previous attempts to construct such a new paradigm of economics have failed. Artificial intelligence, rapidly developing in the 21st century, brought some hope to those seeking to dismantle the classical paradigm of mainstream economics. In this paper, we present our research on the classical paradigm of mainstream economics. We put forward a research hypothesis stating that the mainstream economic paradigm should not be dismantled, but rather modified. We propose applying data filtering at both the input and output stages to the existing paradigm by constructing various filters. These filters would enable economics to formulate practical conclusions, increase the efficiency of scientific research, allow the discovery of new economic laws, and optimize the decision-making process.